Cryptococcosis: Unusual Presentation in A Patient Suffering of Acute Lymphoblastic Leukemia; Case Report and Review of The Literature - Vitale, Roxana Gabriela (2023)
Cryptococcosis is a disseminated fungal disease especially described in HIV patients, although in other non-HIV hosts such as those with other immunosuppression’s were also described. Cryptococcus neoformans has been reported to be isolated from blood cultures in around 20% of patients with cryptococcosis being correlated with poor prognosis. We report a case of HIV negative patient suffering from acute lymphoblastic leukemia (ALL) CD20+, treated with GATLA 2020 AYA protocol that developed disseminated cryptococcosis. Liposomal amphotericin was initiated to treat the fungal disease. However, despite antifungal therapy the patient died within 5 days. Literature on invasive fungal infections in ALL cases is also reviewed, with particular attention to cryptococcosis.